Investigation of Violent Theft Crimes That Caused the Death of People (Case Study LP/15/K/VII/2018/Sek at the Pariangan Tanah Datar Police) - Arief Hidayat; Yoserwan Yoserwan; Nani Mulyati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to find out and analyze investigations into criminal acts of theft with violence that resulted in the death of people and to find out and analyze the obstacles encountered and the efforts made by investigators in carrying out investigations into criminal acts of theft with violence which Resulted in the death of people at LP/15/K/VII/2018 in the Legal Area of the Pariangan Police, Tanah Datar. The problem focused on how investigators tried to overcome the obstacles encountered during the investigation on LP/15/K/VII/2018 in the Pariangan Tanah Datar Police Legal Area. In this article, what is used as a legal research method is normative-empirical, namely legal research based on legal research that not only examines the normative system of laws and regulations but also observes the reactions and interactions that occur when the normative system works or is implemented in the society under study. This article is descriptive, in which this study aims to clarify and validate the case studied. The data were obtained through document studies and direct interviews with Investigator Ipda Lian Tanjung at the Pariangan Tanah Datar Police who handled the case and were analyzed qualitatively.